Case studies in spiritual care - Nash, Paul, 1959-; Todd, Andrew, 1961- (Jessica Kingsley Publishers, 2018)
Through a rich variety of case studies, this book provides insight into the patient's needs and the chaplain's perspective, as well as discussions of spiritual assessments and spiritual care interventions. Case studies such as a request to baptise a child complicated due to his admission for 'psychiatric reasons', as well as work with military veterans, such as a female transgender veteran who has been alienated from her faith, show the breadth and complexity of work that chaplains undertake daily. Each section also includes critical responses to the case studies presented from a chaplain and related healthcare professional. This book will enable chaplains to critically reflect on the spiritual care they provide, and provide an informed perspective for healthcare professionals and others involved in chaplaincy services.